1987
DOI: 10.1104/pp.84.4.1451
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Characteristics of a Photoautotrophic Cell Suspension Culture of Soybean

Abstract: ABSTRACrA soybean suspension culture (SB-P) which can grow photoautotrophically in 5% CO2 will not grow in ambient CO2 levels. This elevated CO2 requirement seems to be due to the additive effects of a number of factors. The in vivo activity of ribulose-1,5-bisphosphate carboxylase (RuBPcase) is much lower in the SB-P cells, compared to soybean plants. This may be due to the low light intensity used to culture the cells, which has been shown to decrease both the amount and activity in whole plants, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 14 publications
3
37
0
1
Order By: Relevance
“…This may reflect, in part, the health of the cells or the stage of the growth cycle (22). Dark respiration rates were generally higher than the 6 to 7 ,mol C/mg Chl h reported for a soybean leaf (19).…”
Section: Carbonic Anhydrasementioning
confidence: 73%
See 2 more Smart Citations
“…This may reflect, in part, the health of the cells or the stage of the growth cycle (22). Dark respiration rates were generally higher than the 6 to 7 ,mol C/mg Chl h reported for a soybean leaf (19).…”
Section: Carbonic Anhydrasementioning
confidence: 73%
“…Soybean (Glycine max) cells and high C02-requiring cotton (Gossypium hirsutum) cells were grown at 5% C02 in a modified MS medium2 which contained thiamine and hormones as the only organic compounds (22). Cells were subcultured every 2 weeks.…”
Section: Photoautotrophic Cell Suspension Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The percent activation, ranging from 16 to 53% in these current experiments, has likewise been found to be lower compared with leaf cells. The activation of Rubisco for growth chamber grown spinach leaves was approximately 86%, and greenhouse grown soybean leaves were reported to be 95% activated (3,21,25). However, recent studies with the COT-P and SB 1-P cells demonstrated that Rubisco could be activated to higher levels of 93 to 94% with a 5-min preillumination prior to assaying for Rubisco activity (20).…”
Section: Photosynthetic Enzyme Activitymentioning
confidence: 99%
“…Volaina) were grown hydroponically in a growth chamber in half-Hoagland nutrient solution (Arnon, 1950) Cell suspension growth conditions.-Photosynthetic cell suspensions from soybean (Glycine max var. Corsoy) SB-P line were grown as described by Rogers et al (1987) with some modifications. These cell suspensions were established in our laboratory in 1990.…”
Section: Methodsmentioning
confidence: 99%